Sexist language determinants in two local magazines / Ramesh Nair - Nair, Ramesh (2002)
The English language is regarded by many as a catalyst for development in many developing countries. Though this is true, it is a language that has its roots in a patriarchal society and because of this, it is flawed to a certain degree. Feminists and linguists alike have long argued that the English language discriminates against women, specifically, with the usage of sexist language. No society can claim itself to be progressive if the language being used in that society becomes the very tool that discriminates against a particular group of people. This study analyses the usage of sexist language by writers in two local magazines. Selected sentences written by female and male writers for a gender specific audience were presented to respondents in a questionnaire. Data gathered from the analysis of the questionnaires were used to investigate what determined the usage of sexist language in the corpus. The analysis revealed that it was the gender of the target audience rather than the writer's gender that determined the usage of sexist language. In addition, the analysis also revealed that language defined as sexist by western feminist were not regarded as such by the respondents.